RESECTION OF AMELOBLASTOMA FOLLOWED BY RECONSTRUCTION WITH NONVASCULARISED ILIAC BONE GRAFT–A CASE REPORT - Tariq Javed; Waqar Jeelani (Journal of University Medical & Dental College, 1970)
ABSTACT Ameloblastoma is benign but locally invasive odontogenic tumor. More than eighty percent of cases of ameloblastoma occur in mandible. A substantial number of the patients of ameloblastoma present when the tumor has significantly grown in size resulting in severe malocclusion, facial asymmetry and pathological fractures of the jaw. There are several types of amelablastomas but the correct diagnosis can be easily made with the help of plain x-rays and tissue biopsy. The standard management of amelobastoma is marginal resection but some times a large tumor requires complete resection of affected part of mandible. This results in a large defect causing significant facial disfigurement. The case presented here involves a young lady with the chief complaint of facial asymmetry and inability to chew the food. A diagnosis of unicysticameloblastoma was made on biopsy and resection of mandible was carried out. The mandibular reconstruction was carried out in the same surgery with non-vascularized iliac bone graft. Long term prognosis showed satisfactory healing and good facial aesthetics.